2016
DOI: 10.1049/iet-pel.2015.0477
|View full text |Cite
|
Sign up to set email alerts
|

Intensive random carrier pulse width modulation for induction motor drives based on hopping between discrete carrier frequencies

Abstract: The existing random carrier pulse-width modulation (RCPWM) schemes result in poor non-deterministic characteristics. They basically use a single-frequency triangular carrier and its inverted version to synthesise the random carrier by a pseudo-random binary sequence (PRBS) bit selector. Even though the bits are highly random in nature with large pattern repetition rate, the resulting random carrier does not possess required level of randomness. Rather it can make slight positional variation in the resulting PW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The generation of pseudo-random signals and SVPWM were implemented on an FPGA-based electric drive in [20], which demonstrated that RSFPWM can spread the spikes of line voltage harmonics to nearby frequencies. For the purpose of enhancing the harmonic power spreading ability of RSFPWM, multiple carriers based RSFPWM is proposed in [21] to improve the randomness of the switching frequency. In [22], due to the excellent performance of RSFPWM in reducing harmonic peaks, RSFPWM is introduced to interior permanent magnet synchronous machine (IPMSM) sensorless control based on high-frequency signal injection to spread out the additional harmonics, yielding a 20dB attenuation in the power peak of full-spectrum.…”
Section: A Variable Switching Frequency Modulation Strategiesmentioning
confidence: 99%
“…The generation of pseudo-random signals and SVPWM were implemented on an FPGA-based electric drive in [20], which demonstrated that RSFPWM can spread the spikes of line voltage harmonics to nearby frequencies. For the purpose of enhancing the harmonic power spreading ability of RSFPWM, multiple carriers based RSFPWM is proposed in [21] to improve the randomness of the switching frequency. In [22], due to the excellent performance of RSFPWM in reducing harmonic peaks, RSFPWM is introduced to interior permanent magnet synchronous machine (IPMSM) sensorless control based on high-frequency signal injection to spread out the additional harmonics, yielding a 20dB attenuation in the power peak of full-spectrum.…”
Section: A Variable Switching Frequency Modulation Strategiesmentioning
confidence: 99%
“…Conventional RCFM techniques usually employ pseudo-random number generation methods based on the use of linear congruence or look-up table methods [22]. Compared with ideal random numbers, pseudo-random numbers may be larger than or smaller than the mathematical expectation within local time periods, which results in the generated randomized carrier frequency being successively larger or smaller than the initial carrier frequency [23]. This imbalance will not maximize the suppression of sideband harmonics to further suppress the sideband vibro-acoustics [24][25][26], and it will result in large current ripples in the output signal of the system, thereby causing output torque fluctuations and the generation of additional switching losses [27].…”
Section: Introductionmentioning
confidence: 99%
“…In order to destroy the fixed pattern in the deterministic SVPWM strategy, the switching frequency/period, the zero-vector distribution ratio, and the pulse positioning pattern should vary according to some specific deterministic or probability distribution laws. Consequently, the nondeterministic SVPWM strategy can be divided into three foundational schemes: random/variable switching frequency PWM [23][24][25][26][27][28][29], random pulse position PWM [30] and random zero-vector distribution [31,32]. The combination of any two fundamental schemes or the three schemes results in the hybrid random PWM scheme [33].…”
Section: Introductionmentioning
confidence: 99%